The Relationship of Entrepreneurs and Ruler in SPA Prostitution Business Practices during the Covid-19 Pandemic in the Nodal Region - Syaifudin, Syaifudin; Purwanto, Agung; Budi, Setia (Edumaspul: Jurnal Pendidikan, 2023)
The SPA business is proliferating in Indonesia, almost every city in Indonesia has SPA prostitution. The existence of SPA prostitution violates the regulations of the Tourism Law. However, the SPA prostitution business actors know strategies on how to keep their business running, including during the COVID-19 pandemic. The type of research used by researchers in this research is qualitative research. This research was conducted in 2022 in the Jabodetabek nodal area. The type of sampling used by researchers in this research is non-probability sampling because not everyone in this study can be used as a sample. Meanwhile, the sampling technique for selecting informants in this study used a purposive sampling technique. Primary data collection was carried out through interviews and observations. Meanwhile, secondary data was collected using data sources through literature studies and documentation. Based on the field findings, it can be concluded that these SPA prostitution entrepreneurs have built relationships with the authorities around which the SPA prostitution business is carried out. These authorities can be local government officials and also members of mass organizations. The relationship that SPA prostitution entrepreneurs build with the authorities is for no other purpose than protecting and securing their prostitution business practices so that they are not disturbed. The relationship between entrepreneurs and those in power at the wheels of business is a problem introduced previously in the academic context, but this concept is interesting to discuss.